Association between speeding and use of alcohol and medicinal and illegal drugs and involvement in road traffic crashes among motor vehicle drivers. (17th November 2018) - Jørgenrud, Benedicte; Bogstrand, Stig Tore; Furuhaugen, Håvard; Jamt, Ragnhild E. G.; Vindenes, Vigdis; Gjerde, Hallvard
Abstract: Objective: The objective of this study was to study the association between self-reported road traffic crashes (RTCs) and recent use of alcohol and medicinal and illicit drug use and self-reported speeding in the previous 2 years. Methods: During the period from April 2016 to April 2017, drivers of cars, vans, motorcycles, and mopeds were stopped in a Norwegian roadside survey performed in collaboration with the police. Participation was voluntary and anonymous. The drivers were asked to deliver an oral fluid sample (mixed saliva), which was analyzed for alcohol and 39 illicit and medicinal drugs and metabolites. In addition, data on age, sex, and self-reported speeding tickets and RTCs during the previous 2 years were collected. Results: A total of 5, 031 participants were included in the study, and 4.9% tested positive for the use of one or more illicit or medicinal drugs or alcohol. We found a significant, positive association between the use of cannabis and RTC involvement (odds ratio [OR] = 1.93; 95% confidence interval [CI], 1.05–3.57; P = 0.035) and also between previous speeding tickets and RTC involvement (OR = 1.39; 95% CI, 1.08–1.80; P = 0.012). In addition, older age groups were found to have a significant, negative association with RTC involvement, with ORs equal to or less than 0.49, when using the age group 16–24 as reference. Conclusion: Speeding, as an indicator of risk behavior, and the use of cannabis were associated with previous RTC involvement, whereas increasing age was significantly associated with lower risk. This is consistent with previous studies on RTCs.